Use and outcome of liver transplantation in acetaminophen-induced acute liver failure - William Bernal; Julia Wendon; Mohamed Rela; Nigel Heaton; Roger Williams (1998)
Once defined clinical criteria are fulfilled in acetaminophen-induced hepatotoxicity, prognosis without orthotopic liver transplantation (OLT) may be very poor. In the present study, we examined the application and outcome of OLT in 548 patients admitted to a single center between 1990 and 1996. Four hundred twenty-four (77%) of the patients studied did not fulfill transplantation criteria, and 396 of these (93%) survived. The majority of the 28 nonsurvivors (7%) in this group fulfilled two of three combined criteria, and the finding of a high APACHE III score could be used as an indicator for the need for OLT. Of the 56 patients (45%) not listed, in only a small proportion was this caused by psychiatric reasons, and in the majority, it was a consequence of the rapid development of multiple organ failure and cerebral edema. This also applied to 24 (35%) of the 68 listed patients in whom the rapidity of clinical deterioration, reflected in increasing APACHE III scores, was such that even with the prompt availability of donor organs, OLT was not possible. In the final event, only 44 (35%) of those who fulfilled criteria underwent OLT, of whom 33 (75%) survived to leave the hospital. Survival was greatest in those receiving unreduced grafts, and markers of early graft function differed significantly between survivors and nonsurvivors. Liver transplantation is an effective treatment in a relatively small number of patients with acetaminophen-induced hepatotoxicity, and for a substantial proportion, transplantation was never an option because of the rapidity of clinical deterioration. APACHE III scoring may be of value in decision making and in better defining patients in clinical trials.